Effects of investigator disturbance on the reproductive success of Short-tailed Sheerwaters Puffinus tenuirostris. - Carey, Mark James. (2011)
Thesis (Ph.D.) - La Trobe University, 2011 Submission note: "A thesis submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy [to the] School of Life Sciences, Faculty of Science, Technology and Engineering, La Trobe University, Bundoora".